Controles na liberdade de expressao: a 1ª Conferência Nacional de Comunicação na imprensa - Massuda, Arthur Serra (2013)
This research reviews the Brazilian press reports on the First National Conference on Communications (Confecom). It combines concepts from Michel Foucault‟s discourse theory, particulary his concept of procedures on discourse control, and Ernesto Laclau and Chantal Mouffe‟s political theory of discourse. The selection of press reports on Confecom included those from newspapers Folha de S.Paulo, O Estado de S. Paulo and O Globo, in December 2009, when the conference took place. The review reveals a journalistic discourse controlled by an end-oriented rationality, constituting an invisible space around violations of freedom of expression denounced by the conference. The research included analysis on documents from the Confecom Organizing Commission, in order to assess how debates were expected to occur. Results reveal a debate where discourses were divided into thematic axis and work groups, while their effectiveness is controlled by vote procedures. A model of public debate where the press is a protagonist, i.e. subjects articulating journalistic techniques express themselves through mainly private means of communication, can be found on recommendations from the Organization of American States‟ inter-American system of freedom of expression and is designed based on democratic needs. In these recommendations, democracy is analogue to a utilitarian liberalism that Foucault points out on government practices during 18th century, aiming the management of public and private interests. Among the democratic needs, the journalistic quest toward public interest is questioned as it demands specific configuration on the political economy of communications in order to work properly. Otherwise, it is always vulnerable to an overdetermination of particular interests on this quest. On the other hand, by maintaining an unsolvable public-private antagonism, such liberal position, though a necessity to the inter-American-recommended democracy, does not measure up to the radical democracy need advocated by Mouffe on The Democratic Paradox, meaning the inclusion of those excluded from and by political processes. In the conclusion, an effort to constitute a public debate to achieve this need is developed based on Axel Honneth theory of recognition. On such a debate, journalistic discourse is controlled by a resistance to experiences of disrespect